Original paperNon-surgical septal reduction by coil embolization in patients with hypertrophic obstructive cardiomyopathy. An alternative to alcohol ablation - Dąbrowski, Maciej; Witkowski, Adam; Brzozowski, Krzysztof; Konka, Marek; Śpiewak, Mateusz; Chojnowska, Lidia S. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2011)
Dynamic obstruction of the left ventricular outflow tract is present in 25-30% of patients with Hypertrophic Cardiomyopathy (HCM). The non-surgical method of interventricular septum thickness reduction using coils is a new technique of percutaneous treatment in patients with hypertrophic obstructive cardiomyopathy (HOCM). The presented method could be an interesting alternative for left ventricular outflow tract pressure gradient reduction in patients with HOCM in whom alcohol ablation may be related to a higher risk of complications. We present a description of two patients with HOCM and drug-refractory symptoms, who underwent closure of the septal branch using coils in the Institute of Cardiology.